2014
DOI: 10.1089/end.2013.0662
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Body Wall on Lithotripter Shock Waves

Abstract: Purpose: Determine the influence of passage through the body wall on the properties of lithotripter shock waves (SWs) and the characteristics of the acoustic field of an electromagnetic lithotripter. Methods: Full-thickness ex vivo segments of pig abdominal wall were secured against the acoustic window of a test tank coupled to the lithotripter. A fiber-optic probe hydrophone was used to measure SW pressures, determine shock rise time, and map the acoustic field in the focal plane. Results: Peak positive press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
2
1
Order By: Relevance
“…Second, a thinner KT resulted in a poorer treatment outcome. This observation differed particularly from those of other studies, most of which showed that a greater tissue thickness/SSD resulted in a poorer treatment result [ 12 , 13 ]. We postulated that these two findings were due to an effect of renal cortical scarring on SW transmission.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…Second, a thinner KT resulted in a poorer treatment outcome. This observation differed particularly from those of other studies, most of which showed that a greater tissue thickness/SSD resulted in a poorer treatment result [ 12 , 13 ]. We postulated that these two findings were due to an effect of renal cortical scarring on SW transmission.…”
Section: Discussioncontrasting
confidence: 91%
“…In the clinical study by Hammad and Balakrishnan [ 16 ], KT and MT were combined for the analysis, and the effect of KT on the efficacy of SWL might therefore not be demonstrated. For the other in vivo and in vitro studies, the degree of renal cortical scarring in relatively young pigs compared with that in our study patients, who had a mean age of 50 years, might have hampered the demonstration of an effect of the renal cortex on SW transmission [ 12 , 13 , 15 ]. This difference in the composition of tissues may explain the inconsistent effects of SSD reported in different studies.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation